Effect of ginger extract as green inhibitor on chloride-induced corrosion of carbon steel in simulated concrete pore solutions. (20th March 2019) - Liu, Yongqi; Song, Zijian; Wang, Wanyi; Jiang, Linhua; Zhang, Yingjie; Guo, Mingzhi; Song, Fengyan; Xu, Na
Abstract: In this study, we tried to employ the ginger extract as an environmentally friendly inhibitor to improve chloride-induced corrosion resistance of reinforcing steel in simulated concrete pore solutions. The inhibiting performances of ginger extract as well as three other inhibiting systems were studied by stereo-microscope and various electrochemical measures. The main phenolic compounds of ginger extract were confirmed by liquid chromatography-mass spectrometry. Meanwhile, the elements and chemical bonds existed in the surface passive film of the steel bar immersed in the ginger inhibiting system were characterized via attenuated total reflection Fourier transform infrared spectroscope (ATR-FTIR) and X-ray photoelectron spectroscopy (XPS). Electrochemical results indicated that the ginger extract was an efficient corrosion inhibitor in reducing the chloride-induced corrosion and at the optimal dosage (2%) it could improve the chloride threshold values of steel electrodes from 0.02 mol/L to 0.08 mol/L. From the results of potentiodynamic polarization, ATR-FTIR and XPS, it was found that the ginger extract was a mixed type corrosion inhibitor that improved the corrosion resistant performance of carbon steel mainly by forming a carbonaceous organic film to restrain both the cathodic and the anodic corrosion reaction. Highlights: We innovatively employed ginger extract as an environmentally friendly inhibitor in SCP solutions. Ginger extract has been confirmed as an effective mixed-type corrosion inhibitor by various electrochemical measures. Results from ATR-FTIR and XPS confirmed the formation of the carbonaceous organic film on the steel bar.